Implementasi dan Problematika Program Merdeka Belajar Serta Kampus Merdeka Pada Lembaga Pendidikan Islam - Anisa Anisa; Cindy Elvira; Muhammad Khair (Cakrawala: Journal of Religious Studies and Global Society, 2025)
This article discusses the implementation and problems of the Independent Learning and Independent Campus (MBKM) Program in Islamic educational institutions. The purpose of this study is to identify challenges and solutions in implementing the program in Islamic educational environments. The method used is a literature study with data collection from various related sources. The results of the study indicate that although MBKM provides opportunities for students to develop competencies, there is a gap between Islamic values and modern educational approaches. Therefore, innovative curriculum management, improving educator competency, and integrating technology are needed to overcome this problem. The conclusion of this study emphasizes the importance of collaboration between stakeholders in optimizing the implementation of MBKM in Islamic educational institutions.